Penile Rehabilitation and Treatment Options for Erectile Dysfunction Following Radical Prostatectomy and Radiotherapy: A Systematic Review - Nicolai, Melianthe; Urkmez, Ahmet; Sarikaya, Selcuk; Fode, Mikkel; Falcone, Marco; Albersen, Maarten; Gul, Murat; Hatzichristodoulou, Georgios; Capogrosso, Paolo; Russo, Giorgio Ivan (Frontiers in Surgery, 2021)
After radical prostatectomy (RP) or radiotherapy (RT) for prostate cancer, erectile dysfunction (ED) is the main complication, highly effecting quality of life. The pathophysiology of ED after these treatments is believed to include neuropraxia causing reduced oxygenation and structural changes of the tissue in the corpora cavernosa. Next to the option of sparing the nerves during RP, research have been focusing on methods for penile rehabilitation after RP and RT, since it occurs often, even after nerve sparing techniques were used. In animal studies, use of phosphodiesterase type 5 inhibitors (PDE5i) after cavernous nerve damage is supported, but results in human studies are contradictory. Non-medical treatment options such as vacuum device therapy, hyperbaric oxygen therapy, yoga, aerobic or pelvic floor training may be helpful but evidence is scare. Therefore, guidelines for penile rehabilitation are not available up until to date. But care and support for ED after RP and RT is highly demanded by a large group of patients, so measures have to be taken even though the evidence is not strong yet. In this systematic review an overview of the literature for penile rehabilitation and treatment options for ED after RP and RT is provided, using only randomized controlled trials (RCT), in order to give some guidance for the clinical practice until better studies are available.